Властивості матрицанта лінійної системи з фіксованими моментами імпульсної дії - Петришин, Р.I.; Сопронюк, Т.М. (Нелінійні коливання, 2011)
На основании оценки матрицанта линейной системы без импульсного воздействия получена экспоненциальная оценка матрицанта соответствующей системы с фиксированными моментами импульсного воздействия. Исследовано также поведение частных производных этого матрицанта по малому параметру ε. Using an estimate for the matriciant of a linear system without impulsive effects, we find an exponential estimate for the matriciant of the corresponding system with impulsive effects occurring at fixed times. The behaviour of the partial derivatives of this matriciant with respect to a small parameter ε is examined.